2006
DOI: 10.1089/thy.2006.16.1229
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Differentiated Thyroid Carcinoma Following Initial Therapy

Abstract: This analysis was performed to determine the effect of initial therapy on the outcomes of thyroid cancer patients. The study setting was a prospectively followed multi-institutional registry. Patients were stratified as low risk (stages I and II) or high risk (stages III and IV). Treatments employed included near-total thyroidectomy, administration of radioactive iodine, and thyroid hormone suppression therapy. Outcome measures were overall survival, disease-specific survival, and disease-free survival. Near-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
483
4
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 597 publications
(514 citation statements)
references
References 55 publications
13
483
4
14
Order By: Relevance
“…More recent data from a prospectively followed, but nonrandomized cohort of patients with thyroid cancer has shown improved overall and disease-specific survival with TSH suppression in those stratified as having high-risk disease (13). Furthermore, suppression of TSH to an undetectable limit was associated with the greatest benefit.…”
Section: Introductionmentioning
confidence: 99%
“…More recent data from a prospectively followed, but nonrandomized cohort of patients with thyroid cancer has shown improved overall and disease-specific survival with TSH suppression in those stratified as having high-risk disease (13). Furthermore, suppression of TSH to an undetectable limit was associated with the greatest benefit.…”
Section: Introductionmentioning
confidence: 99%
“…In this study no further datasmall carcinomas, presumably for lack of events. Another study by the National Cooperative Thyroid Cancer Treatment Study Group demonstrated a beneficial effect of radioiodine therapy in all patients except those with stage I disease [17]. Unfortunately, group I in this study consisted of a large sample of young patients with the disease extent varying from microcarcinomas to microscopic extraglandular invasion or cervical lymph node metastases.…”
mentioning
confidence: 84%
“…Препаратом выбора является лево-тироксин [1, 2, [138][139][140][141][142][143][144][145][146][147][148][149][150][151][152].…”
Section: терапия левотироксиномunclassified